Cover Image. Issue 7 (28th October 2022) - Mirhaj, Marjan; Labbaf, Sheyda; Tavakoli, Mohamadreza; Seifalian, Alexander Marcus
Abstract: The cover image is based on the Review Article Emerging treatment strategies in wound care by Marjan Mirhaj et al., https://doi.org/10.1111/iwj.13786 . Abstract : The cover image is based on the Review Article Emerging treatment strategies in wound care by Marjan Mirhaj et al., https://doi.org/10.1111/iwj.13786 .